A Multi-Dimensional Approach to Suicide Bombing - Gill, Paul (International Journal of Conflict and Violence (IJCV), 2007)
Understanding suicide bombing entails studying the phenomenon on three different dimensions: the suicide bomber, the terrorist organization, and the com- munity from which suicide bombings emerge. Political and social psychology allow us to establish the reciprocal relationships that underpin the exchanges between the three dimensions. This method increases our theoretical understanding of suicide bombing by moving away from the unidimensional models that have previously dominated the terrorism literature.